The complete mitogenome of Gracilaria chouae and its phylogenetic analysis - Tang, Xianming (Mitochondrial DNA B Resour, 2019)
Gracilaria chouae, a marine red macroalgae, is a rich source of active substances and is listed as biological and health food material with high economic value. The mitogenome sequence of G. chouae is 25,829 bp. A total of 50 genes were determined, including 24 protein-encoding genes, two rRNA genes, 23 tRNA genes, and one unidentified open reading frame (ORF). Phylogenetic analysis showed that G. chouae clustered together with Gracilariopsis chorda, Gracilariopsis lemanaeformis, Gracilariopsis andersonii, Gracilariophila oryzoides, and Gracilariopsis heteroclada. The mitogenome analysis will help the understanding of Gracilaria evolution.